2010
DOI: 10.1111/j.1445-2197.2009.05132.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma: differences in presentation between different ethnicities in the New Zealand setting

Abstract: These results show that MPIs have a more advanced local NPC disease than Asians at presentation, and that for specific T stages, the nodal disease is also more advanced than that found in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…1 Similar to our study, in New Zealand, Asians presented at a lower stage than Maori and Pacific Islanders. 13 Three studies using SEER registry data reported improved OS among Chinese subjects compared with other ethnicities. 6,8,14 One study found that the improved OS was not only due to histology, as Chinese patients with keratinizing squamous cell carcinoma also had improved outcomes compared with white patients with this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…1 Similar to our study, in New Zealand, Asians presented at a lower stage than Maori and Pacific Islanders. 13 Three studies using SEER registry data reported improved OS among Chinese subjects compared with other ethnicities. 6,8,14 One study found that the improved OS was not only due to histology, as Chinese patients with keratinizing squamous cell carcinoma also had improved outcomes compared with white patients with this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and radiologic findings alone are not sufficient to give a definitive diagnosis. 3,7,8 The most common tumor-like lesion in the nasopharynx is adenoid hypertrophy. Adenoid hypertrophy is mostly seen in the pediatric age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar symptoms might also be seen in benign tumor-like lesions. 7 Soft tissue thickening seen on CT, ulcerations, or necrosis of mucosa on endoscopy generally indicates a malignant process; however, no imaging finding is 100% diagnostic. In order to determine the nature of a lesion, biopsy and detailed histopathologic examination must be performed.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Previous research, limited to the Auckland region, reported that nasopharyngeal cancer disproportionally affects Māori, Pacific peoples and Asian populations 13 , 14 and reported on differences in extent of disease at diagnosis. 15 Ethnic diversification of Aotearoa New Zealand in recent decades coupled with advances in molecular detection, imaging techniques and optimised chemoradiation strategies underscores the importance of an updated review. Little is also known about survival outcomes for patients with nasopharyngeal cancer in Aotearoa New Zealand, and prognostic factors relevant to our population have not been defined.…”
Section: Introductionmentioning
confidence: 99%